Binomial Logistic Regression Analysis of Hypertension Based on 4 Risk Factors and 2 Protective Factors Based on Simultaneous Test of Omnimbus Likelihood Ratio - febry istyanto (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2023)
Background: Hypertension is one of the most common and dangerous non-communicable diseases in the world. The prevalence of hypertension in Indonesia reaches 34.1% and is the main cause of premature death and disability. Research Metodes: This study aims to determine the biopsychosocial relationship to the incidence of hypertension. Results: Hypertension is influenced by anxiety (OR= 7.45; 95% CI= 2.35 to 23.66; p<0.001), stress (OR= 2.95; 95% CI= 1.14 to 7.63; p=0.026) , sleep quality (OR= 8.15; 95% CI= 3.04 to 21.83; p<0.001), family history (OR= 2.83; 95% CI= 1.11 to 7.19; p=0.029) , physical activity (OR= 0.118; 95% CI= 0.038 to 0.367; p<0.001), vegetable and fruit consumption (OR= 0.20; 95% CI= 0.06 to 0.59; p=0.003). Conclusion: anxiety, stress, sleep quality, family history, physical activity, consumption of vegetables and fruit affect the incidence of hypertension. Keywords: Hypertension, Binomial, Biopsychosocial.